Effect of Secretome-Hypoxia Mesenchymal Stem Cells on Regulating SOD and MMP-1 mRNA Expressions in Skin Hyperpigmentation Rats - Zukhiroh, Zukhiroh; Putra, Agung; Chodidjah, Chodidjah; Sumarawati, Titiek; Subchan, Prasetyowati; Trisnadi, Setyo; Hidayah, Nurul; Amalina, Nur Dina (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Ultraviolet B (UVB) radiation is the main factor causing hyperpigmentation. MSC secretome contains bioactive soluble molecules such as cytokines and growth factors that can accelerate skin regeneration. However, the molecular role of the secretome in hyperpigmentation is still unclear. AIM: This study aimed to determine the effect of secretome hypoxia mesenchymal stem cells (S-HMSC) gel on the expression of superoxide dismutase (SOD) and matrix metalloproteinases (MMP-1) genes in skin tissue of hyperpigmented rats induced by UVB light exposure. MATERIALS AND METHODS: Experimental research with post-test only control group. The control, base gel, T1 and T2 groups were UVB irradiated 6 times in 14 days at 302 nm with an minimal erythema dose of 390 mJ/cm2, respectively, while sham group did not receive UVB exposure. T1 was given 100 uL of S-HMSC gel and T2 was given 200 uL of S-HMSC gel every day for 14 days, while base gel received base gel. On day 15, skin tissue was isolated and analyzed for SOD and MMP-1 expression using qRT-PCR. RESULTS: The relative expression of the SOD gene in the treatment group (P1 = 0.47 ± 0.20, P2 = 1.22 ± 0.47) increased with increasing dose compared to the control group (UVB = 0.05 ± 0.01, Base gel = 0.05 ± 0.02). The relative expression of the MMP-1 gene in the treatment group (T1 = 5.82 ± 1.16, T2 = 2.86 ± 1.57) decreased with increasing dose compared to the control group (Control = 10.10 ± 2.31, and Base gel = 9.55 ± 1.29). CONCLUSION: Administration of S-HMSC gel can increase SOD gene expression and decrease MMP-1 gene expression in skin tissue of hyperpigmented rats model induced by UVB light.